2020
DOI: 10.1101/2020.08.11.20171108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2 expression in adipose tissue is associated with COVID-19 cardio-metabolic risk factors and cell type composition

Abstract: COVID-19 severity has varied widely, with demographic and cardio-metabolic factors increasing risk of severe reactions to SARS-CoV-2 infection, but the underlying mechanisms for this remain uncertain. We investigated phenotypic and genetic factors associated with subcutaneous adipose tissue expression of Angiotensin I Converting Enzyme 2 (ACE2), which has been shown to act as a receptor for SARS-CoV-2 cellular entry. In a meta-analysis of three independent studies including up to 1,471 participants, lower adip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 73 publications
3
16
1
1
Order By: Relevance
“…Despite the contention that ACE2 expression may be upregulated in white adipose tissue (WAT), enabling WAT to serve as a functional reservoir for SARS-CoV-2 in obese individuals ( Ledford, 2020 ), data supporting this hypothesis are limited ( Figure 4 ). Gene expression profiles from 1,471 male and female individuals (ages 35–85) across three human datasets demonstrated lower ACE2 expression in subcutaneous WAT from individuals with obesity or T2D relative to control subjects ( El-Sayed Moustafa et al., 2020 ). Notably, expression of ACE2 and TMPRSS2 was relatively low in subcutaneous WAT and ACE2 expression was higher with increasing age.…”
Section: Sars-cov-2 Entry Factors and Adipose Tissuementioning
confidence: 99%
“…Despite the contention that ACE2 expression may be upregulated in white adipose tissue (WAT), enabling WAT to serve as a functional reservoir for SARS-CoV-2 in obese individuals ( Ledford, 2020 ), data supporting this hypothesis are limited ( Figure 4 ). Gene expression profiles from 1,471 male and female individuals (ages 35–85) across three human datasets demonstrated lower ACE2 expression in subcutaneous WAT from individuals with obesity or T2D relative to control subjects ( El-Sayed Moustafa et al., 2020 ). Notably, expression of ACE2 and TMPRSS2 was relatively low in subcutaneous WAT and ACE2 expression was higher with increasing age.…”
Section: Sars-cov-2 Entry Factors and Adipose Tissuementioning
confidence: 99%
“…ACE2 expression is high in adipose relative to other tissues (60) and adipocyte expression of ACE2 is upregulated in obesity and DM. Increased expression of ACE2 in adipose tissue has been linked to worse clinical outcomes of COVID‐19 (61,62). In summary, these observations suggest a potential mechanism for SARS‐CoV‐2 viral adipotropy.…”
Section: Adipose Tissue As a Target For Sars‐cov‐2 Infectionmentioning
confidence: 99%
“…This could be explained by an imbalance in the RAAS system secondary to obesity [ 59 ], and possibly linked to robust systemic response secondary to SARS-CoV-2 infection. Recent meta-analysis showed that individuals with lower level of ACE2 expression in adipose tissue are more likely to be associated with type 2 diabetes mellitus, cardiovascular comorbidities, metabolic syndrome, and a higher body mass index, which are all risk factors of severe COVID-19 [ 60 ].…”
Section: Ace2 Expression and Obesitymentioning
confidence: 99%